2021
DOI: 10.1111/pedi.13283
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: Influence of center size on quality of diabetes control in children and adolescents with type 1 diabetes—A longitudinal analysis of the DPV cohort

Abstract: Background Treatment of patients with type 1 diabetes requires experience and a specific infrastructure. Therefore, center size might influence outcome in diabetes treatment. Objective To analyze the influence of center size on the quality of diabetes treatment in children and adolescents in Germany and Austria. Patients and methods In 2009 and 2018, we analyzed metabolic control, acute complications, and rates of recommended screening tests in the DPV cohort. Diabetes centers were classified according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…Our results are in concordance with a previous study from the national DPV Registry in Germany and Austria, showing the lowest number of consultations in the smallest hospitals 10 . All‐cause hospitalisation in relation to hospital volume has not been studied previously.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are in concordance with a previous study from the national DPV Registry in Germany and Austria, showing the lowest number of consultations in the smallest hospitals 10 . All‐cause hospitalisation in relation to hospital volume has not been studied previously.…”
Section: Discussionsupporting
confidence: 92%
“…All‐cause hospitalisation in relation to hospital volume has not been studied previously. However, the previous study revealed that diabetic ketoacidosis (DKA) occurred most in extra‐small centres (<20 patients), while DKA and hypoglycaemia rates were lowest in extra‐large centres (≥200 patients) 10 . This indicates a similar hospitalisation pattern that aligns with our results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations